Systematic Reviews in Neonatal Respiratory Care: Are Some Conclusions Misleading? - Maturana, Andres; Moya, Fernando; Donn, Steven M. (Frontiers in Pediatrics, 2020)
An increasing amount of information is currently available in neonatal respiratory care. Systematic reviews are an important tool for clinical decision-making. The challenge is to combine studies that address a specific clinical question and have similar characteristics in terms of populations, interventions, comparators, and outcomes, so that their combined results provide a more precise estimate of the effect that can be validly extrapolated into clinical practice. The concept of heterogeneity is reviewed, emphasizing that it should be considered in a wider perspective and not just as a mere statistical test. A case is made of how well-designed studies of the neonatal respiratory literature, when equivocally combined, can provide very precise but potentially biased results. Systematic reviews in this field and others should be rigorously peer-reviewed before publication to avoid misleading readers to potentially biased conclusions.